"Never Again": Fascism and Anti-Fascism in Melbourne in the 1990s. (May 2019) - Fox, Vashti Jane
Abstract : An upsurge of fascist and anti-fascist activity in Australia in the early part of the twentieth century has received sustained historical attention. Yet scholarly historical coverage of the latter part of the century has been minimal. This article demonstrates the ongoing existence of both a far-right movement and a concomitant anti-fascist opposition by focusing on Melbourne in the 1990s. It draws from interviews with anti-fascist activists and from campaign paraphernalia and press reports. It introduces the group National Action (NA), identifies its political tactics and shows how it rebranded fascist traditions from Europe and the USA by drawing on iconic figures and symbols of the Australian labour movement, anti-immigrant racist tropes and on white Australian nationalism. Anti-fascist groups were loose collections of left activists and organisations animated by memories of the racist horrors of World War II. This article shows that, over time, loosely affiliated ant-fascist groups were influenced by various overseas currents of thought about political practice. These included notions of a United or Popular Front, direct and indirect action, "no platforming" and "squaddism" respectively. The analysis draws on contemporary trends in international anti-fascism studies.